Super Porous Carboxymethyl Cellulose–Tannic Acid (TA@CMC) Cryogels with Antioxidant, Antibacterial, and α-Glucosidase Enzyme Inhibition Abilities - Mehtap Sahiner; Sahin Demirci; Nurettin Sahiner (Polysaccharides)
Here, super porous carboxymethyl cellulose (CMC) cryogels were synthesized in 10–100% crosslinker and the presence of TA, at varying amounts of TA, e.g., 10 and 25 wt% of CMC under cryogenic conditions (−20 °C) as TA@CMCs. To control the degradation of CMC cryogel networks, the crosslinking ratio of divinyl sulfone (DVS:X) to CMC varied at 10, 25, 50, and 100% moles of the CMC repeating unit. Higher hydrolytic degradation was observed for CMC 10%X cryogels at pH 1.0 with 28.4 ± 1.2% weight loss. On the other hand, the TA-release studies from TA@CMC-based cryogels showed that higher TA releases were observed for both TA@CMC 10% and 25% cryogels at pH 7.4, with 23.6 ± 1.1, and 46.5 ± 2.3 mg/g in 480 min, which are equal to almost 24% and 18% of the TA contents of the corresponding cryogels, respectively. The antioxidant properties of TA@CMC cryogels were examined, and worthy antioxidant properties were observed due to the TA. The alpha-glucosidase enzyme inhibition ability of the prepared cryogels was examined at different concentrations by grinding cryogels, and it was determined that TA@CMC 25% cryogel at 3 mg/mL concentration inhibited 70.4 + 1.3% of the enzyme. All bare CMC-based cryogels were found to be non-hemolytic with a less than 1% hemolysis ratio and also effective on the blood coagulation mechanism with blood-clotting index (BCI) values between 62.1 and 81.7% at 1 mg/mL concentrations. On the other hand, TA@CMC 25% cryogels exhibited a slight hemolytic profile with a 6.1 ± 0.8% hemolysis ratio and did not affect the blood coagulation mechanism with 97.8 ± 0.4% BCI value.